ANALISIS KOMPARATIF PENERAPAN HIGHER ORDER THINKING SKILLS DALAM SOAL UJIAN SEKOLAH PENDIDIKAN AGAMA ISLAM TAHUN 2025 - Arbani Arbani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to comparatively analyze the application of Higher Order Thinking Skills (HOTS) in three sets of Islamic Religious Education (PAI) School Examination questions in 2025 in three different regions: Rantau Pulung, Bengalon, and North Sangatta. Using the descriptive-comparative content analysis method, this study examined the proportion of HOTS questions, question characteristics, distribution of cognitive levels, and integration of contemporary issues in PAI learning evaluation instruments. The results showed the consistency of the proportion of HOTS questions in the three regions (33.33%-37.8%) with the dominance of the cognitive level of analyzing (C4), while the level of creating (C6) is still minimal. All three sets of questions showed success in contextualizing PAI materials and integrating contemporary issues, especially environmental and socio-economic issues. This study recommends increasing the proportion of creating level (C6) questions, developing more diverse stimulus questions, and strengthening interdisciplinary connections between PAI and other fields of study for a more comprehensive evaluation of PAI learning